Food waste composting with the addition of Sabah ragi using passive aeration-auto turning composter - Mohd Al Mussa Ugak (2023)
Organic wastes generated can cause environmental problems if not treated properly. In-vessel Composting is an alternative biological treatment method used to convert waste into a stabilized, valuable end-product. However, identifying the process biodegradation mechanism and the uncertainty measures in controlling the system are critical for good performance. Thus, the purposes of this study were to determine the optimum turning frequency and ragi dosage, its kinetic analysis based on volatile solids, evaluate the performance of passively aerated in-vessel composting process, examine the effect of compost on the plant growth and to determine the feasibility of composting system in terms of economic analysis. Four sets of experiments (TF for every 0, 1, 3, and 5 days) were conducted to investigate turning frequency (TF). Four different ragi compositions were studied: 0 g (control), 0.5 g, 1.0 g and 1.5 g ragi/200 g initial compost using a compost bottle with turning every three days for 15 days. The elemental kinetics of the process were determined using zero-, first-, second- and n-order equations. Subsequently, the optimum condition obtained from the experiments were used for passively aerated in-vessel composting process. Food waste and dry leaves (2.6:1 by weight) composting process was conducted in two trials for 40 days. The physical, chemical, biological and morphological changes that occurred during the composting process were identified and evaluated. The power consumption during the composting process was also evaluated. Dwarf crape jasmine (Tabernaemontana divaricata) were grown in media containing compost and top soil with nine different proportion (0%, 2.5%, 5%, 10%, 20%, 30%, 40%, 50%, or 100% of compost) and the plant growth was measured for 90 days. Based on organic matter loss, the turning frequency of every three days and 1.0 g ragi/200 g of the initial compost resulted in the highest OM loss of 79.2% and 61.3%, respectively. The n-order model successfully estimated the degradation profile for 3-days TF and 1.0 g ragi/200 g of the initial compost with rate constant value (k) of 8 x 10-5 VS(1-n). day-1 and 1.30 x 10(1-n) VS-1.day-1, respectively. For passively in-vessel composting process, the highest average compost temperatures of 54.2 °C and 46.7 °C were recorded on days 7 and 10 of Trials 1 and 2, respectively. The highest average heat generation rate per initial mass of compost dry matter of 4098 kJ kg−1 day−1 was achieved on day 7. In this study, application of the second-order model resulted in good responses with rate constant (k) of 0.0003 TOC-1.day-1 and 0.0002 TOC-1.day-1 for Trials 1 and 2, respectively. The pH value increased while the electrical conductivity decreased during the composting process for both trials. The TOC decreased from 50.3% to 37.1% and 47.8% to 38.8% and the mass reduction after 40 days of composting process is 72% and 65% from the total weight of the feedstock for trial 1 and 2, respectively. In terms of mass balance, the mass reduction was mainly due to water evaporation, leachate, excess moisture and dry matter loss and gas emissions. The total average mass reduction and compost produced was ~67% and ~27 % of the initial mass, respectively. The average power consumption of 6.78 kWh was observed for one cycle of a composting process. Low pathogens level and higher nitrogen content were detected in the final compost while some of the nutrients are not in the recommended range. Among the treatments, the 5%-30% compost mixture shows the greatest growth development. Results in this study indicate that food waste composting can be used to promote dwarf crape jasmine growth. Kinetic obtained is essential to determine waste biodegradability and develop a valuable measure for the loss of organic matter during composting. Based on the cost analysis, the applicability of composting system in UMS is economically feasible and could possibly generate a profit of RM 14,824.61 per year.